Sosioalisasi Pelayanan Prima Kepada Laundry Cahaya Terang - Nirmalawati, Nirmalawati; Monique Ds, Eska Prima; Febriansa, M Rahman; Yudi, Yudi; Nasution, Suswati (Jurnal Dehasen Mengabdi, 2024)
This study explores the implementation of strategies for providing excellent customer service at "Cahaya Terang" laundry. Through literature review, case studies, and interviews with business owners and managers, the research identifies key practices for enhancing customer experience in laundry services. Results highlight the significance of employee training, efficient workflow management, quality control measures, and customer feedback mechanisms. The study underscores the importance of integrating these elements to cultivate a culture of customer-centricity and ensure sustained business success. Practical implications and recommendations for stakeholders, including business owners, employees, and customers, are also discussed.